2018
DOI: 10.3892/ol.2018.8861
|View full text |Cite
|
Sign up to set email alerts
|

A meta‑analysis of transcriptome datasets characterizes malignant transformation from melanocytes and nevi to melanoma

Abstract: Melanoma represents one of the most aggressive malignancies and has a high tendency to metastasize. The present study aims to investigate the molecular mechanisms of two pathways to cancer transformation with the purpose of identifying potential biomarkers. Our approach is based on a meta-analysis of gene expression profiling contrasting two scenarios: A model that describes a transformation pathway from melanocyte to melanoma and a second model where transformation occurs through an intermediary nevus. Data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The less favorable prognoses are obviously linked to the more advanced stages of the disease. In recent years, many studies have shed light on the mechanisms underlying melanoma development and have shown that the melanocytes tumor transformation process is complex and multi-stage [ 19 , 20 ]. It is clear that the most benign lesions present the alteration of v-Raf murine sarcoma viral oncogene homolog B (BRAF) in the codon V600E (that is sufficient for the nevus formation), but for melanoma development, BRAF mutation is not sufficient because the disease progression is bound to concomitant alteration in other genes involved in the most important cellular processes [ 21 , 22 ].…”
Section: Metastatic Melanomamentioning
confidence: 99%
“…The less favorable prognoses are obviously linked to the more advanced stages of the disease. In recent years, many studies have shed light on the mechanisms underlying melanoma development and have shown that the melanocytes tumor transformation process is complex and multi-stage [ 19 , 20 ]. It is clear that the most benign lesions present the alteration of v-Raf murine sarcoma viral oncogene homolog B (BRAF) in the codon V600E (that is sufficient for the nevus formation), but for melanoma development, BRAF mutation is not sufficient because the disease progression is bound to concomitant alteration in other genes involved in the most important cellular processes [ 21 , 22 ].…”
Section: Metastatic Melanomamentioning
confidence: 99%
“…In recent years, several large-scale transcriptomic and genomic studies have identified deregulated lncRNAs in melanomas [60,61]. In a study using a collection of 7256 RNAsequencing libraries from 27 tissues and cancer types, 339 lncRNAs were associated with melanoma [62].…”
Section: Oncogenic Lncrnas In Melanomamentioning
confidence: 99%
“…Immunohistochemistry and genetic studies, as well as analyses of patient serum, have highlighted these differences and could be incorporated to aid diagnosis. For example, malignant melanomas express higher levels of CXCL1, CXCL2, and CXCL8 and receptors CXCR1, CXCR4, CCR10, and CCR7 compared with benign naevi [ 108 , 109 , 110 , 111 ]. The expression of chemokines such as CXCL8 and its receptor CXCR2 increase as the tumour transitions from the radial to the vertical growth phase [ 24 ].…”
Section: How Can Chemokines Be Exploited Therapeutically?mentioning
confidence: 99%